The Relationship Between the Use of Short Form Vidoes on Social Media and the Attention Span of Students in the Class of 2022, Faculty of Medicine, Universitas Prima Indonesia - Siena Sanjana Dhillon; Clarissa Lister; Juliana Lina (Journal of Social Research, 2025)
The rise of social media has popularized short-form videos (SFVs) like TikTok, Instagram Reels, and YouTube Shorts among university students. Excessive exposure to SFV content may affect behavioral patterns, particularly attention span, which plays a vital role in academic performance. This study aimed to examine the patterns of SFV usage, assess students’ attention spans, and determine the relationship between SFV use and attention span among 2022 medical students at Universitas Prima Indonesia. Using a quantitative analytical design with a cross-sectional approach, data were collected through questionnaires from 200 respondents and analyzed using univariate and bivariate methods with the Chi-Square test. Statistical analysis was performed at a significance level of ? = 0.05, with the Chi-Square test yielding p < 0.05 as the criterion for significant associations. Results revealed that 85.5% of students had high SFV usage, primarily through TikTok (56.5%), with daily viewing exceeding 3 hours (65%) and weekly viewing exceeding 14 hours (53%). Lifestyle (62.5%) and entertainment (59%) were the most-watched content types. Attention span levels were classified as good (48%) and poor (52%), and statistical analysis showed a significant correlation between SFV usage and attention span (p = 0.000). The study recommends promoting digital literacy, time management, and responsible media consumption among students, alongside further research on SFV impacts on cognition and mental health.